Manchild dan Representasi Maskulinitas dalam Kepemimpinan Politik - Alma Shafuramah; Fadia Rosa Amalia; Ika Arinia Indriyany (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
The behavior of political leaders in the public sphere influences how society evaluates leadership quality. In recent years, the term manchild has been used to describe adult men who show emotional or defensive responses when facing criticism. This study aims to analyze the phenomenon of manchild in contemporary politics by examining its relation to patriarchy, hegemonic masculinity, and political communication. This research uses a qualitative approach with a literature review method. Data were obtained from relevant books, scientific journals, and articles, then analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The findings show that the manchild phenomenon in politics is not only related to the personal character of political leaders, but is also influenced by patriarchal structures and hegemonic masculinity that shape expectations of male leadership. The “foreign stooges” narrative in political speeches shows that responses to criticism can function as a political communication strategy as well as an effort to maintain leadership image in the public sphere